KORELASI MODEL HUBUNGAN DUA VARIABEL DENGAN ANALISIS REGRESI SPLINE - Hazmira Yozza; Afrimayani Afrimayani (Jurnal Matematika UNAND, 2019)
This paper discussed about the construction of a model the relationship between a dependent variabel and a independent variabel using spline analysis regression. This methods is usually used when the relationship between variables is unknown. This methods is applied to construct the growth curve for children under 3 years of age in Padang.Kata Kunci: spline regression, growth curve, children under 3 years of age